A broad complex tachycardia suggesting global ischemia or repolarization abnormalities. Issue 4 (2nd June 2021) - Gkalapis, Charis; Papadakis, Marios; Martin, Claire A.; Bazoukis, George; Letsas, Konstantinos P.; Vlachos, Konstantinos
Abstract : Our case presents a ​cavotricuspid isthmus (CTI​)‐dependent atrial flutter (AFL) with 1:1 atrioventricular conduction and pronounced ST‐segment elevation in aVR, previously described as a "shark fin phenomenon, " mimicking a broad complex tachycardia with a ventricular origin.